Analysis method for composite crack initiation toughness of bonding interface of common concrete and ultra-high performance concrete bonding material under different loading rates

Through the experimental-numerical method combined with the double-material straight-groove semi-Brazilian disc sample and the separated Hopkins press rod model, the problem of low accuracy and time-consuming calculation of cracking toughness in the bonding interface of ordinary concrete and ultra-high performance concrete is solved, and higher calculation accuracy and efficiency are achieved.

CN119595537APending Publication Date: 2025-03-11CHANGZHOU ARCHITECTUAL RES INST GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411609548.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, when calculating the cracking toughness of the bonding interface of ordinary concrete and ultra-high performance concrete bonding materials, there are problems of low accuracy and long time.

Method used

Using the experimental-numerical method, a double-material straight-groove semi-Brazil disc sample was prepared and a separate Hopkins compression rod model was constructed, and a three-point bending dynamic test was carried out to obtain the test data at different loading rates, and a loading rate value x-compound cracking toughness KCSIF analysis model was constructed through curve fitting.

Benefits of technology

The accuracy of the calculation results of the cracking toughness of the material composite is improved and the time it takes to calculate the results is shortened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595537A_ABST
    Figure CN119595537A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material performance analysis, in particular to a method for analyzing the composite crack initiation toughness of a bonding interface of a common concrete and ultra-high performance concrete bonding material under different loading rates. Constructing a model; placing a sample on the model, and inputting different loading rates by utilizing a three-point bending dynamic test so as to output test data under each loading rate; calculating the crack initiation toughness of the first sub-composite and the crack initiation toughness of the second sub-composite; calculating to obtain composite crack initiation toughness; constructing a loading rate value-composite crack initiation toughness analysis model; the composite crack initiation toughness of the bonding surface of the bonding material under the corresponding loading rate value x is obtained. According to the method, the loading rate value x-composite crack initiation toughness analysis model is constructed, so that the composite crack initiation toughness of the bonding surface of the bonding material under the corresponding loading rate value can be obtained, the accuracy of the calculation result of the composite crack initiation toughness of the material can be improved, and the time consumed by the calculation result of the composite crack initiation toughness of the material can be shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material performance analysis, and in particular to an analysis method for composite cracking toughness of a bonding interface of a combination material of ordinary concrete and ultra-high performance concrete under different loading rates. Background Art

[0002] Crack initiation toughness refers to the stress intensity factor K caused at the crack tip when the external load reaches the crack initiation load. It is a fracture parameter that characterizes the ability of the structure to resist crack expansion when the material cracks. The factors affecting crack initiation toughness include: material properties (for example: physical properties such as material toughness, strength, hardness, etc.), specimen size, specimen material, initial crack length, initial crack position, loading method (for example: tension, compression, bending, etc.), loading rate. Crack initiation toughness is of great significance in engineering applications. It can not only serve as a basis for structural design and material selection, but also as a basis for evaluating the safety and stability of the structure. During the construction process, by monitoring the changes in crack initiation toughness, potential crack problems can be discovered and dealt with in a timely manner, thereby ensuring the safety and stability of the structure.

[0003] Normal Concrete (NC) is a traditional material with excellent performance and is widely used in modern civil engineering structures. However, with the increase of service life, ordinary concrete structures will suffer varying degrees of damage or destruction under the increasing loads, long-term physical, chemical and biological factors. Ultra-high performance concrete (Ultra-High Performance Concerte (with steel fiber, UHPC), Plian Ultra-High Performance Concrete (without steel fiber, PUHPC)) has excellent properties such as ultra-high strength, ultra-high toughness, and ultra-high durability. It is an advanced cement-based composite material and a promising reinforcement and repair material for damaged reinforced concrete structures. A large number of studies have shown that although the use of ultra-high performance concrete materials can effectively overcome the problems of debonding and large shrinkage caused by ordinary concrete materials, various defects are prone to exist near the bonding surface of ordinary concrete and ultra-high performance concrete, resulting in the interface strength being far lower than the matrix strength. At the same time, under the influence of the external environment, stress concentration and residual stress are also very likely to occur at the bonding surface, making the stress at the bonding position of the two (i.e., the bonding surface of the concrete and ultra-high performance concrete bonding materials) high, thus causing the bonding surface to become the weak point of this type of paving method. The initiation and expansion of cracks in this part are also very likely to cause different degrees of damage to the structure, which will affect the service life of the entire structure. Therefore, the analysis of the composite cracking toughness of the bonding surface of ordinary concrete and ultra-high performance concrete bonding materials under different loading rates has become extremely urgent, which is of great significance for ensuring the safety and stability of ordinary concrete materials and ultra-high performance concrete bonding structural materials under various loading rate impacts.

[0004] At present, the measurement methods of fracture toughness include:

[0005] 1. Empirical method: The crack initiation toughness is estimated based on the relationship between the stress intensity factor at the crack tip and the critical stress intensity factor, and the ratio of the external load to the peak load;

[0006] 2. Test method: By measuring the initial fracture load of the specimen, the crack initiation toughness is calculated using the linear elastic fracture mechanics formula;

[0007] However, the empirical method lacks a theoretical basis and its accuracy is subject to certain limitations. The experimental method is relatively accurate but requires a certain amount of time and resources. Summary of the invention

[0008] The technical problem to be solved by the present invention is: in order to solve the technical problems that the calculation results of the composite cracking toughness of existing materials have low accuracy and long time consumption, the present invention provides an analysis method for the composite cracking toughness of the bonding interface of ordinary concrete and ultra-high performance concrete bonding materials under different loading rates. By improving the calculation method of the composite cracking toughness of materials, the accuracy of the calculation results of the composite cracking toughness of materials can be improved, and the time consumed for the calculation results of the composite cracking toughness of materials can be shortened.

[0009] The technical solution adopted by the present invention to solve the technical problem is: an analysis method for the composite cracking toughness of the bonding interface of ordinary concrete and ultra-high performance concrete bonding materials under different loading rates, comprising the following steps:

[0010] S1. Preparation of dual-material straight-cut groove half-Brazilian disc specimens;

[0011] S2, construct a split Hopkins pressure bar model;

[0012] S3, obtaining the double-material straight-cut groove half-Brazilian disc specimen in step S1 and the separated Hopkins pressure bar model in step S2, and placing the double-material straight-cut groove half-Brazilian disc specimen on the separated Hopkins pressure bar model, and inputting different loading rates using a three-point bending dynamic test to output test data at each loading rate;

[0013] S4, obtaining the test data at each loading rate in step S3, and using the experimental-numerical method to calculate the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2 at the prefabricated crack tip of the dual-material straight-cut groove half-Brazilian disc specimen at the time of crack initiation;

[0014] S5, obtaining the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2 in step S4, and calculating the composite crack initiation toughness K of the bi-material straight-cut groove half-Brazilian disc specimen under different loading rates through the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2. CSIF ;

[0015] S6. Obtain the composite crack initiation toughness K of the bi-material straight-cut groove half-Brazilian disc specimen at different loading rates in step S5. CSIF , and construct the loading rate value x-composite cracking toughness K by curve fitting CSIF Analytical models;

[0016] S7, obtaining the loading rate value x in step S6 - the composite cracking toughness K CSIF The analysis model is used to analyze the bonding surface of ordinary concrete and ultra-high performance concrete bonding materials under different loading rates to output the composite cracking toughness K of the bonding surface of the bonding material corresponding to the loading rate value x. CSIF .

[0017] Therefore, the first sub-composite cracking toughness K1 and the second sub-composite cracking toughness K2 of the bi-material straight-cut groove half-Brazilian disk specimen are obtained by the experimental-numerical method, and then the composite cracking toughness K CSIF , the final construction loading rate value x-composite cracking toughness K CSIF The analytical model can be used to obtain the composite cracking toughness K of the bonding surface of the bonding material at the corresponding loading rate x when the loading rate value is known. CSIF This method can improve the accuracy of the calculation results of the composite cracking toughness of the material and shorten the time required for the calculation results of the composite cracking toughness of the material.

[0018] Furthermore, the step S1 includes the following steps:

[0019] S1-1. Pour ordinary concrete material into an EVA mold to form an ordinary concrete sub-sample with a cross-sectional shape of 1 / 4 circle;

[0020] S1-2, obtaining the ordinary concrete sub-sample in step S1-1, and performing a smoothing treatment on the bonding surface of the ordinary concrete sub-sample to obtain a roughened ordinary concrete sub-sample;

[0021] S1-3, obtaining a common concrete sub-sample after roughening in step S1-2, and casting an ultra-high performance concrete sub-sample in an EVA mold to obtain a dual-material straight-cut groove half-Brazilian disc sample without cutting prefabricated seams and without sharpening treatment;

[0022] S1-4, obtaining the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample in step S1-3, and sequentially performing a curing treatment, a demoulding treatment, and a re-curing treatment on the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample;

[0023] S1-5, obtaining the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample processed in step S1-4, and performing a cutting process on the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample to obtain a unsharpened double-material straight-cut groove half-Brazilian disc sample;

[0024] S1-6. Obtain the unsharpened dual-material straight-cut groove half-Brazilian disc sample in step S1-5, and sharpen the unsharpened dual-material straight-cut groove half-Brazilian disc sample to obtain a dual-material straight-cut groove half-Brazilian disc sample.

[0025] Further, in step S1-4, the curing treatment refers to: covering the surface of the double material straight-cut groove half-Brazilian disc sample with a plastic film, and controlling the temperature of the double material straight-cut groove half-Brazilian disc sample to 20°C, and the relative humidity to be greater than 50%; the re-curing treatment refers to: immersing the double material straight-cut groove half-Brazilian disc sample after the demolding treatment in 20°C water for 28 days, and the relative humidity is greater than 95%.

[0026] Further, in step S2, the split Hopkins pressure bar model includes: a sample impact system and a data acquisition system, and the sample impact system and the data acquisition system are connected.

[0027] Further, in step S2, the sample impact system includes: an impact rod, an incident rod, a projection rod, an absorption rod and an absorber, and the impact rod, the incident rod, the projection rod, the absorption rod and the absorber are distributed in sequence; the double-material straight-cut groove half-Brazilian disc specimen is located between the incident rod and the projection rod; the impact rod is provided with an air valve chamber, a shaper is provided on the side of the incident rod close to the impact rod, the incident rod is provided with a first strain gauge G1, and the projection rod is provided with a second strain gauge G2.

[0028] Furthermore, in step S2, the data acquisition system includes: a dynamic strain gauge, a velocimeter, a digital oscilloscope and a data processing system, the dynamic strain gauge and the velocimeter are both connected to the digital oscilloscope, and the digital oscilloscope is connected to the data processing system; the first strain gauge G1 and the second strain gauge G2 are both connected to the dynamic strain gauge, the dynamic strain gauge is used to collect the strain pulse-time waveform of the first strain gauge G1 and the strain pulse-time waveform of the second strain gauge G2, the velocimeter is used to collect the impact velocity of the impact rod, and the digital oscilloscope is used to obtain the crack initiation load of the dual-material straight-cut groove half-Brazilian disc specimen.

[0029] Furthermore, in step S3, the test data includes: crack initiation time and crack initiation load.

[0030] Furthermore, the step S4 comprises the following steps:

[0031] S4-1, obtaining the crack initiation time corresponding to the crack initiation load during the whole destruction process of the double-material straight-cut groove half-Brazilian disc specimen in step S3;

[0032] S4-2. Construction of a full-scale model based on a bi-material straight-cut groove half-Brazilian disc specimen;

[0033] S4-3. Obtain the crack initiation time corresponding to the crack initiation load during the entire destruction process of the dual-material straight-cut groove half-Brazilian disc specimen in step S3 and the full-size model based on the dual-material straight-cut groove half-Brazilian disc specimen in step S2, and input the crack initiation time corresponding to the crack initiation load into the full-size model based on the dual-material straight-cut groove half-Brazilian disc specimen, and use the experimental-numerical method to output the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2 of the prefabricated crack tip of the dual-material straight-cut groove half-Brazilian disc specimen at the crack initiation time.

[0034] Further, in step S5, the composite fracture toughness K CSIF The calculation formula is:

[0035]

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The first sub-composite cracking toughness K1 and the second sub-composite cracking toughness K2 of the bi-material straight-cut groove half-Brazilian disc specimen are obtained by the experimental-numerical method, and then the composite cracking toughness K CSIF , the final construction loading rate value x-composite cracking toughness K CSIF The analytical model can be used to obtain the composite cracking toughness K of the bonding surface of the bonding material at the corresponding loading rate x when the loading rate value is known. CSIF This method can improve the accuracy of the calculation results of the composite cracking toughness of the material and shorten the time required for the calculation results of the composite cracking toughness of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0039] Figure 1 It is a flow chart of the method for analyzing the composite cracking toughness of the bonding interface of ordinary concrete and ultra-high performance concrete bonding materials under different loading rates of the present invention;

[0040] Figure 2 is a flow chart of step S1 of the present invention;

[0041] Figure 3 is a flow chart of step S4 of the present invention;

[0042] Figure 4 It is a configuration diagram of a dual-material straight-cut groove half-Brazilian disc specimen of the present invention;

[0043] Figure 5 This is a scanning result diagram of the roughness of the bonding surface of the NC material of the double-material straight-cut groove half-Brazilian disc specimen of the present invention;

[0044] Figure 6This is a processing effect diagram of a double-material straight-cut groove half-Brazilian disc sample of the present invention;

[0045] Figure 7 It is a structural schematic diagram of the separated Hopkins pressure bar model of the present invention;

[0046] Figure 8 A schematic diagram of the crack propagation and crack initiation time of the present invention;

[0047] Fig. 9 It is a structural schematic diagram of a sample and a separated Hopkins compression bar model in the numerical calculation process of the present invention;

[0048] Fig.10 It is a fitting curve diagram of the composite cracking toughness of the bonding interface of the ordinary concrete and ultra-high performance concrete bonding material under different loading rates of the present invention.

[0049] In the figure: 1. sample impact system; 101. impact rod; 1011. valve chamber; 102. incident rod; 1021. first strain gauge G1; 103. projection rod; 1031. second strain gauge G2; 104. absorption rod; 105. absorber; 2. data acquisition system; 201. dynamic strain gauge; 202. velocimeter; 203. digital oscilloscope; 204. data processing system. DETAILED DESCRIPTION

[0050] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, which only illustrate the basic structure of the present invention in a schematic manner, and therefore only show the components related to the present invention.

[0051] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0052] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0053] like Figures 1 to 10 As shown in FIG. 1 , it is the best embodiment of the present invention. The analysis method of the composite cracking toughness of the bonding interface of ordinary concrete and ultra-high performance concrete bonding materials under different loading rates in this embodiment includes the following steps:

[0054] S1. Preparation of Bi-materrial Notch Semi-Circular Brazilian disc (BNSCB);

[0055] S2, construct a split Hopkins pressure bar model;

[0056] S3, obtaining the double-material straight-cut groove half-Brazilian disc specimen in step S1 and the separated Hopkins pressure bar model in step S2, and placing the double-material straight-cut groove half-Brazilian disc specimen on the separated Hopkins pressure bar model, and inputting different loading rates using a three-point bending dynamic test to output test data at each loading rate;

[0057] S4, obtaining the test data at each loading rate in step S3, and using the experimental-numerical method to calculate the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2 at the prefabricated crack tip of the dual-material straight-cut groove half-Brazilian disc specimen at the time of crack initiation;

[0058] S5, obtaining the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2 in step S4, and calculating the composite crack initiation toughness K of the bi-material straight-cut groove half-Brazilian disc specimen under different loading rates through the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2. CSIF (Compound Stressintensity factor, CSIF);

[0059] S6. Obtain the composite crack initiation toughness K of the bi-material straight-cut groove half-Brazilian disc specimen at different loading rates in step S5. CSIF , and construct the loading rate value x-composite cracking toughness K by curve fitting CSIF Analytical models;

[0060] S7, obtaining the loading rate value x in step S6 - the composite cracking toughness KCSIF The analysis model is used to analyze the bonding surface of ordinary concrete and ultra-high performance concrete bonding materials under different loading rates to output the composite cracking toughness K of the bonding surface of the bonding material corresponding to the loading rate value x. CSIF Therefore, the first sub-composite cracking toughness K1 and the second sub-composite cracking toughness K2 of the bi-material straight-cut groove half-Brazilian disc specimen are obtained by the experimental-numerical method, and then the composite cracking toughness K CSIF , the final construction loading rate value x-composite cracking toughness K CSIF The analytical model can be used to obtain the composite cracking toughness K of the bonding surface of the bonding material at the corresponding loading rate x when the loading rate value is known. CSIF This method can improve the accuracy of the calculation results of the composite cracking toughness of the material and shorten the time required for the calculation results of the composite cracking toughness of the material.

[0061] In this embodiment, step S1 includes the following steps:

[0062] S1-1. Pour ordinary concrete material into an EVA (ethylene vinyl acetate copolymer) mold to form an ordinary concrete sub-sample with a cross-sectional shape of 1 / 4 circle;

[0063] S1-2, obtaining the ordinary concrete sub-sample in step S1-1, and performing a smoothing treatment on the bonding surface of the ordinary concrete sub-sample to obtain a roughened ordinary concrete sub-sample;

[0064] S1-3, obtaining a common concrete sub-sample after roughening in step S1-2, and casting an ultra-high performance concrete sub-sample in an EVA mold to obtain a dual-material straight-cut groove half-Brazilian disc sample without cutting prefabricated seams and without sharpening treatment;

[0065] S1-4, obtaining the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample in step S1-3, and sequentially performing a curing treatment, a demoulding treatment, and a re-curing treatment on the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample;

[0066] S1-5, obtaining the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample processed in step S1-4, and performing a cutting process on the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample to obtain a unsharpened double-material straight-cut groove half-Brazilian disc sample;

[0067] S1-6, obtaining the dual-material straight-cut groove half-Brazilian disc sample that has not been sharpened in step S1-5, and sharpening the dual-material straight-cut groove half-Brazilian disc sample that has not been sharpened to obtain a dual-material straight-cut groove half-Brazilian disc sample;

[0068] In step S1-4, the curing treatment means: the surface of the double material straight groove half Brazilian disc sample is covered by a plastic film, and the temperature of the double material straight groove half Brazilian disc sample is controlled at 20°C and the relative humidity is greater than 50%; the re-curing treatment means: the double material straight groove half Brazilian disc sample after demoulding is immersed in 20°C water for 28 days, and the relative humidity is greater than 95%. For example: the surface roughness of the ordinary concrete sub-sample is measured by an optical profiler (Bruker CountorGT K 3D); the bonding surface of the ordinary concrete sub-sample is smoothed by a steel brush method; the prefabricated seam of the double material straight groove half Brazilian disc sample is cut by a cutting machine with a blade thickness of 0.5 mm; the prefabricated crack tip is sharpened by metal wire drawing.

[0069] In this embodiment, in step S2, the split Hopkins pressure bar model includes: a sample impact system 1 and a data acquisition system 2, and the sample impact system 1 and the data acquisition system 2 are connected; the sample impact system 1 includes: an impact rod 101, an incident rod 102, a projection rod 103, an absorption rod 104 and an absorber 105, and the impact rod 101, the incident rod 102, the projection rod 103, the absorption rod 104 and the absorber 105 are distributed in sequence; the double-material straight-cut groove half-Brazilian disc sample is located between the incident rod 102 and the projection rod 103; the impact rod 101 is provided with an air valve chamber 1011, the incident rod 102 is provided with a shaper on the side close to the impact rod 101, the incident rod 102 is provided with a first strain gauge G11021, and the projection rod 103 is provided with a second strain gauge G21031; the data acquisition system 2 includes: a dynamic strain gauge 201, a velocimeter 202, a digital oscilloscope 203 and a data processing system 204, the dynamic strain gauge 201 and the velocimeter 202 are both connected to the digital oscilloscope 203, and the digital oscilloscope 203 is connected to the data processing system 204; the first strain gauge G11021 and the second strain gauge G21031 are both connected to the dynamic strain gauge 201, the dynamic strain gauge 201 is used to collect the strain pulse-time waveform of the first strain gauge G11021 and the strain pulse-time waveform of the second strain gauge G21031, the velocimeter 202 is used to collect the impact velocity of the impact rod 101, and the digital oscilloscope 203 is used to obtain the crack initiation load of the dual-material straight-cut groove half-Brazilian disc specimen. Specifically, the impact velocity of the impact rod 101 collected by the velocimeter 202 can reflect the loading rate of the dual-material straight-cut groove half-Brazilian disc specimen; the cracking load of the dual-material straight-cut groove half-Brazilian disc specimen can be obtained through the strain pulse-time waveform of the first strain gauge G11021 and the strain pulse-time waveform of the second strain gauge G21031.

[0070] Specifically, during the test, the impact rod 101 is accelerated by nitrogen pressurization, and the impact rod 101 impacts the incident rod 102 to generate an incident wave. When the incident wave reaches the interface between the incident rod 102 and the double-material straight-cut groove semi-Brazilian disc specimen, due to the different wave impedances of the two materials (concrete material and ultra-high performance concrete material), a reflected wave and a transmitted wave are generated, wherein: the reflected wave enters the incident rod 102, and the transmitted wave enters the transmission rod 103. The waveforms of the incident wave and the reflected wave can be collected through the first strain gauge G1 1021, and the transmitted wave can be collected through the second strain gauge G2 1031. When the incident wave and the reflected wave pass through the first strain gauge G1 1031 attached to the surface of the incident rod 102, 1021. When the transmitted wave passes through the position of the second strain gauge G21031 pasted on the surface of the transmission rod 103, its voltage signal will change, and the data acquisition system 2 will respectively collect the corresponding monitoring voltage signals. Based on the one-dimensional stress wave theory, the monitored voltage signals can be analyzed and calculated, and finally the cracking load of the dual-material straight-cut groove half-Brazilian disc specimen can be obtained.

[0071] In this embodiment, in step S3, the test data includes: crack initiation time and crack initiation load.

[0072] In this embodiment, step S4 includes the following steps:

[0073] S4-1, obtaining the crack initiation time corresponding to the crack initiation load during the whole destruction process of the double-material straight-cut groove half-Brazilian disc specimen in step S3;

[0074] S4-2. Construction of a full-scale model based on a bi-material straight-cut groove half-Brazilian disc specimen;

[0075] S4-3, obtaining the crack initiation time corresponding to the crack initiation load during the whole process of the double material straight groove half Brazilian disc specimen failure in step S3 and the full-scale model based on the double material straight groove half Brazilian disc specimen in step S2, and inputting the crack initiation time corresponding to the crack initiation load into the full-scale model based on the double material straight groove half Brazilian disc specimen, and outputting the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2 of the prefabricated crack tip of the double material straight groove half Brazilian disc specimen at the crack initiation time by using the experimental-numerical method. For example: using ABAQUS software to establish a full-scale model of the double material straight groove half Brazilian disc specimen.

[0076] In this embodiment, in step S5, the composite fracture toughness K CSIF The calculation formula is:

[0077]

[0078] It should be noted that: due to K CSIF =K1+K2 has a real part and an imaginary part. Therefore, the absolute value K is used to express the composite cracking toughness K of the bi-material straight-cut groove half-Brazilian disc specimen. CSIF .

[0079] The following is an example of a double-material straight-cut half-Brazilian disc specimen with a diameter of 76 mm, a thickness of 30 mm, a pre-crack length of 10 mm, and a width of 0.5 mm:

[0080] 1. The material properties of the dual-material straight-cut groove half-Brazilian disc specimen are shown in Table 1, the material proportions of the concrete sub-specimen are shown in Table 2, and the material proportions of the ultra-high performance concrete sub-specimen are shown in Table 3;

[0081] 2. The processing results of ordinary concrete sub-samples are shown in Figures 1 and 2;

[0082] 3. The number and serial number of the bi-material straight-cut half-Brazilian disc specimens are shown in Table 4;

[0083] 4. The lengths of the impact rod 101, the incident rod 102, and the projection rod 103 are 0.4 m, 2.0 m, and 1.5 m respectively. The diameters of the impact rod 101, the incident rod 102, and the projection rod 103 are all 80 mm. The material is 40CrmoV alloy steel, the elastic modulus is 210, and the Poisson's ratio is 0.25.

[0084] 5. As shown in Figures 5 and 6, one half of the semi-disc model is a Q235 ordinary concrete sub-specimen, and the other half is an ultra-high performance concrete sub-specimen. The diameter of the right support of the dual-material straight-cut groove semi-Brazilian disc specimen is d = 0.5 mm, and the material is the same as that of the SHPB compression rod (both are 40CrmoV alloy steel);

[0085] 6. The setting method of prefabricated cracks in the specimen model adopts the seam type crack preset method embedded in the ABAQUS software. The prefabricated crack tip part uses singular units (1 / 4 node units) to divide the tip unit to eliminate the abnormal stress state of the singular stress shape at the crack tip. The limited area material unit of the crack tip attachment adopts CPS6 unit and mesh encryption, and the other parts adopt CPS8 unit.

[0086] 7. Through the software, with the loading rate x as the X-axis, the composite cracking toughness K CSIF The composite cracking toughness K is fitted to the Y axis CSIF (The applicable range of loading rate x is 163Gpa / s-314Gpa / s) The calculation formula is:

[0087] K CSIF =-0.009x 2 +4.5362x-491.93.

[0088] It should be noted that in the process of solving the fracture parameters, the established models are all two-dimensional models. Since there is no need to simulate the entire process of crack development, no special treatment is performed on the bonding surface of the two half-Brazilian disc specimens with dual materials and straight-cut grooves. It is only necessary to divide the half-disc model into two uniform parts along the center line, and then add the prefabricated crack calculation.

[0089] Table 1 Properties of ordinary concrete materials and ultra-high performance concrete materials

[0090] Concrete Type Dynamic elastic modulus E(MPA) Dynamic Poisson's ratio μ <![CDATA[Density ρ (g / cm 3 )]]> C40 44400 0.28 2.29 PUHPC100 50780 0.22 2.65

[0091] Table 2 Material proportion of concrete sub-sample (unit dosage (Kg / m 3 ))

[0092]

[0093] Table 3 Material proportions of ultra-high performance concrete sub-samples

[0094]

[0095]

[0096] Table 4 Number and number of bi-material straight-cut half-Brazilian disc specimens

[0097]

[0098] In summary, the present invention uses the experimental-numerical method to obtain the first sub-composite cracking toughness K1 and the second sub-composite cracking toughness K2 of the bi-material straight-cut groove half-Brazilian disc specimen, and then obtains the composite cracking toughness K CSIF , the final construction loading rate value x-composite cracking toughness K CSIF The analytical model can be used to obtain the composite cracking toughness K of the bonding surface of the bonding material at the corresponding loading rate x when the loading rate value is known. CSIF This method can improve the accuracy of the calculation results of the composite cracking toughness of the material and shorten the time required for the calculation results of the composite cracking toughness of the material.

[0099] The above description is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. An analysis method for composite cracking toughness of bonding interface between ordinary concrete and ultra-high performance concrete under different loading rates, characterized in that: The following steps are involved: S1. Preparation of dual-material straight-cut groove half-Brazilian disc specimens; S2, construct a split Hopkins pressure bar model; S3, obtaining the double-material straight-cut groove half-Brazilian disc specimen in step S1 and the separated Hopkins pressure bar model in step S2, and placing the double-material straight-cut groove half-Brazilian disc specimen on the separated Hopkins pressure bar model, and inputting different loading rates using a three-point bending dynamic test to output test data at each loading rate; S4, obtaining the test data at each loading rate in step S3, and using the experimental-numerical method to calculate the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2 at the prefabricated crack tip of the dual-material straight-cut groove half-Brazilian disc specimen at the time of crack initiation; S5, obtaining the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2 in step S4, and calculating the composite crack initiation toughness K of the bi-material straight-cut groove half-Brazilian disc specimen under different loading rates through the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2. CSIF ; S6. Obtain the composite crack initiation toughness K of the bi-material straight-cut groove half-Brazilian disc specimen at different loading rates in step S5. CSIF , and construct the loading rate value x-composite cracking toughness K by curve fitting CSIF Analytical models; S7, obtaining the loading rate value x in step S6 - the composite cracking toughness K CSIF The analysis model is used to analyze the bonding surface of ordinary concrete and ultra-high performance concrete bonding materials under different loading rates to output the composite cracking toughness K of the bonding surface of the bonding material corresponding to the loading rate value x. CSIF .

2. The method for analyzing the composite cracking toughness of the bonding interface between ordinary concrete and ultra-high performance concrete under different loading rates according to claim 1 is characterized in that: The step S1 comprises the following steps: S1-1. Pour ordinary concrete material into an EVA mold to form an ordinary concrete sub-sample with a cross-sectional shape of 1 / 4 circle; S1-2, obtaining the ordinary concrete sub-sample in step S1-1, and performing a smoothing treatment on the bonding surface of the ordinary concrete sub-sample to obtain a roughened ordinary concrete sub-sample; S1-3, obtaining a common concrete sub-sample after roughening in step S1-2, and casting an ultra-high performance concrete sub-sample in an EVA mold to obtain a dual-material straight-cut groove half-Brazilian disc sample without cutting prefabricated seams and without sharpening treatment; S1-4, obtaining the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample in step S1-3, and sequentially performing a curing treatment, a demoulding treatment, and a re-curing treatment on the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample; S1-5, obtaining the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample processed in step S1-4, and performing a cutting process on the uncut prefabricated seam and unsharpened double-material straight-cut groove half-Brazilian disc sample to obtain a unsharpened double-material straight-cut groove half-Brazilian disc sample; S1-6. Obtain the unsharpened dual-material straight-cut groove half-Brazilian disc sample in step S1-5, and sharpen the unsharpened dual-material straight-cut groove half-Brazilian disc sample to obtain a dual-material straight-cut groove half-Brazilian disc sample.

3. The method for analyzing the composite cracking toughness of the bonding interface between ordinary concrete and ultra-high performance concrete under different loading rates according to claim 1 is characterized in that: In step S1-4, the maintenance process refers to: The surface of the double-material straight-cut groove half-Brazilian disc specimen is covered with a plastic film, and the temperature of the double-material straight-cut groove half-Brazilian disc specimen is controlled at 20°C and the relative humidity is greater than 50%; Re-maintenance treatment refers to: The demoulded bi-material straight-cut groove half-Brazilian disc specimens were immersed in water at 20°C for 28 days with a relative humidity greater than 95%.

4. The method for analyzing the composite cracking toughness of the bonding interface between ordinary concrete and ultra-high performance concrete under different loading rates according to claim 1 is characterized in that: In step S2, the split Hopkins pressure bar model includes: A sample impact system (1) and a data acquisition system (2), wherein the sample impact system (1) and the data acquisition system (2) are connected.

5. The method for analyzing the composite cracking toughness of the bonding interface between ordinary concrete and ultra-high performance concrete under different loading rates according to claim 4, characterized in that: In step S2, the sample impact system (1) comprises: An impact rod (101), an incident rod (102), a projection rod (103), an absorption rod (104), and an absorber (105), wherein the impact rod (101), the incident rod (102), the projection rod (103), the absorption rod (104), and the absorber (105) are distributed in sequence; The double-material straight-cut groove half-Brazilian disc specimen is located between the incident rod (102) and the projection rod (103); The impact rod (101) is provided with an air valve chamber (1011), a side of the incident rod (102) close to the impact rod (101) is provided with a shaper, the incident rod (102) is provided with a first strain gauge G1 (1021), and the projection rod (103) is provided with a second strain gauge G2 (1031).

6. The method for analyzing the composite cracking toughness of the bonding interface between ordinary concrete and ultra-high performance concrete under different loading rates according to claim 5, characterized in that: In step S2, the data acquisition system (2) comprises: A dynamic strain gauge (201), a speed meter (202), a digital oscilloscope (203), and a data processing system (204), wherein the dynamic strain gauge (201) and the speed meter (202) are both connected to the digital oscilloscope (203), and the digital oscilloscope (203) is connected to the data processing system (204); The first strain gauge G1 (1021) and the second strain gauge G2 (1031) are both connected to the dynamic strain gauge (201); the dynamic strain gauge (201) is used to collect the strain pulse-time waveform of the first strain gauge G1 (1021) and the strain pulse-time waveform of the second strain gauge G2 (1031); the velocimeter (202) is used to collect the impact velocity of the impact rod (101); and the digital oscilloscope (203) is used to obtain the cracking load of the dual-material straight-cut groove half-Brazilian disc specimen.

7. The method for analyzing the composite cracking toughness of the bonding interface between ordinary concrete and ultra-high performance concrete bonding materials under different loading rates according to claim 1, characterized in that: In step S3, the test data includes: Crack initiation time and crack initiation load.

8. The method for analyzing the composite cracking toughness of the bonding interface between ordinary concrete and ultra-high performance concrete bonding materials under different loading rates according to claim 1, characterized in that: The step S4 comprises the following steps: S4-1, obtaining the crack initiation time corresponding to the crack initiation load during the whole destruction process of the double-material straight-cut groove half-Brazilian disc specimen in step S3; S4-2. Construction of a full-scale model based on a bi-material straight-cut groove half-Brazilian disc specimen; S4-3. Obtain the crack initiation time corresponding to the crack initiation load during the entire destruction process of the dual-material straight-cut groove half-Brazilian disc specimen in step S3 and the full-size model based on the dual-material straight-cut groove half-Brazilian disc specimen in step S2, and input the crack initiation time corresponding to the crack initiation load into the full-size model based on the dual-material straight-cut groove half-Brazilian disc specimen, and use the experimental-numerical method to output the first sub-composite crack initiation toughness K1 and the second sub-composite crack initiation toughness K2 of the prefabricated crack tip of the dual-material straight-cut groove half-Brazilian disc specimen at the crack initiation time.

9. The method for analyzing the composite cracking toughness of the bonding interface between ordinary concrete and ultra-high performance concrete under different loading rates according to claim 1, characterized in that: In step S5, the composite fracture toughness K CSIF The calculation formula is: